어깨뼈 내밈 운동 시 어깨관절 수평 벌림과 수평모음 저항과 외부 무게에 따른 앞톱니근, 위등세모근, 그리고 큰가슴근 근활성도 비교 - 배창환; 김규령; 추이저; 김명권; 박수형 (대한정형도수물리치료학회지, 2021)
Background: The increase in the activity of the upper trapezius (UT) muscle and decrease in the activity of the serratus anterior (SA) and lower trapezius (LT) muscle produce an abnormal scapulohumeral rhythem. Therefore, the SA is the focus of therapeutic exercise protocols for the rehabilitation. This study aimed to compare the activity of the muscles according to resistance levels during protraction exercise. Methods: Thirteen healthy 20 to 30 years old male and female subjected participated in the study. All subjects performed the scapular protraction exercise with the weights of 0, 5, and 10㎏, combined with horizontal shoulder abduction and adduction. The electromyography data of the SA, UT, and pectoralis major (PM) during the exercise were recorded using surface electrodes. The ratios of PM/SA and UT/SA were calculated. Repeated one-way ANOVA was used to determine the statistical significance. Results: There was a significant difference in the muscle activity of the SA and PM (p<.05). Specifically, SA had the highest activity and PM had the lowest activity at an abduction resistance 10㎏ (p<.01). There was a significant difference in the ratios of UT/SA and PM/SA (p<.05). The ratio of PM/SA was the lowest at the abduction resistance of 10㎏ (p<.01). Conclusion: According to this study, for the selective activation of the serratus anterior, protraction exercises should be applied as a method of adding resistance to protraction and horizontal abduction.